PARAMETERS OF FLOWS OF GRAIN MATERIALS - KHODIACHIY, VLADYSLAV; NIKITIN, OLEXANDER (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Solving the issue related to the study of flows of loose materials is due to the development of modern sensors of flow parameters of loose materials. In particular, it can be about flow sensors. This type of sensors is one of the most attractive for use in the control and regulation channels of modern automated production control systems in the agricultural and food industry. The issues considered in this article relate to the mechanics of flows of loose materials. The field of mechanics, which studies the static and dynamic aspects of loose materials, is one of the basic branches of mechanics in general. The main focus is on free gravity flow. Grain material is considered as loose material. Taking into account the peculiarities of loose material and the specifics of various industries, the problem of creating flow parameter sensors was and will be relevant. The definition of the object and process for which the sensor is being developed, namely the study of flows of loose materials, is also relevant. The article considered how loose material behaves during free fall from silos in an airless space and also in an airy one. The consumption of bulk materials from the bottom opening of the silo, in most cases, is not stable and leads to the formation of a variable flow of bulk material. After the grain leaves the silos opening, a gravitational flow is formed, consisting of dispersed grains and an air flow. The formed flow of bulk material can be considered as an information factor for determining the consumption of bulk material and a factor in creating effective sensors for automated control systems of technological processes. Formulas for calculating the flow rate of loose material in a gravity flow and the flow volumes at different states were also given in the article.